LEGAL PROTECTION OF TRADE SECRETS AND KNOW-HOW: PROBLEM ASPECTS - Smirnov, Oleksandr (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
The purpose of the article. The issue of legal protection of trade secrets and know-how is very relevant. Therefore, the purpose of this article is to determine the basic premises of the approach to understanding trade secrets and know-how in the current legislation of Ukraine and the problematic aspects of their protection. The methodological basis of the research is general scientific and special methods of cognition. The use of these methods made it possible to describe the problems related to the legal protection of trade secrets and know-how. Results: based on the legal nature of commercial secrets and know-how, the meaning of the «right of access» to these types of confidential information was revealed, as a more adequate term, in contrast to the «right to» commercial secrets and know-how. It was concluded that the subjective right to trade secrets and know-how does not exist, and it is about the protection of the «legally protected interest» of the person who actually controls such information. Discussion: the conditions for the protection of trade secrets and know-how by national legislation remain insufficiently regulated, as evidenced by the judicial practice of Ukraine. The article «Legal protection of trade secrets and know-how: problematic aspects» examines the problematic issues of legal protection of such an atypical object of civil law as trade secrets and know-how, as well as ways to solve them. Based on the specifics of this object of civil law, the meaning of the «right of access» to trade secrets and know-how is revealed as a more adequate term, in contrast to the «right to» information. It was concluded that there is no subjective right to trade secrets and know-how, and it is about protecting the «legally protected interest» of the person who actually controls such information. The legal regime of such objects of civil law as commercial secrets and know-how is not sufficiently described in Ukraine and requires a more detailed study, which should be based on a sound methodological basis. Perhaps that is why the conditions for the protection of commercial secrets and know-how remain insufficiently regulated by national legislation, as evidenced by the judicial practice of Ukraine.